'Roland' or 'Rowland'?. (2nd January 2016) - Gamble, Bob
Abstract : In February 1840 the Brontë sisters gave the Reverend William Weightman a Rowland for his Oliver, in playful response to the valentines he had sent. Their use of the anglicised variant of the name 'Rowland' may have greater significance than previously thought. This article looks more deeply into William Weightman's relationship with the Walton family of Crackenthorpe and other Westmorland figures of the time.